The Effect of Environmental Uncertainty and Financial Distress on Tax Avoidance with Business Strategy as Moderating Variables - Rosalina Nurdiana (Green Publisher Indonesia, 2021)
Tax avoidance is defined as one of the actions taken by taxpayers to reduce their tax burden legally. Tax avoidance is carried out by taking advantage of loopholes in the tax law that are not or have not been regulated, so that it is legal and does not violate the law. The purpose of this study is to analyze the effect of environmental uncertainty on tax avoidance, analyze the effect of financial distress on tax avoidance, analyze the moderating effect of business strategy on the effect of environmental uncertainty on tax avoidance and analyze the moderating effect of business strategy on the effect of financial distress on tax avoidance. This research method is a quantitative method using secondary data. The results of this study indicate that environmental uncertainty has a positive and significant effect on tax avoidance, financial distress has no effect on tax avoidance, business strategies moderate the effect of environmental uncertainty on tax, avoidance, and business strategies cannot moderate the effect of financial distress on tax avoidance.